Literal and Contextual Meanings in Coca-Cola’s Slogans - Felicia Novriella Surjadi; Ivonne Muliawati Harsono (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study aims to reveal the literal and contextual meanings of Coca-Cola’s advertising slogans. This study uses a qualitative method. The writers collected and analyzed the literal and contextual meanings of Coca-Cola advertising slogans, focusing on how each slogan conveyed both literal and contextual meaning. The literal meaning was defined based on the denotative meaning of the words, while the contextual meaning was defined based on the major historical events that happened at the time of the slogan release. The findings show that Coca-Cola utilized their slogans not just as a promotional tool but also to reflect the socio-cultural, political, economic, and business contexts of the time. This study concludes that Coca-Cola has creatively used language to align itself with the situations of the time, which help strengthen the connection with their customers. This validates Coca-Cola’s claims on their website that their slogans were created to reflect the time.